Le primitivisme dramatique de Diderot, un jeu de l’imagination entre nature et culture - Thibaut Julian (Revue Italienne d'Etudes Françaises)
Diderot’s dramatic theory associates the ideas and values of « truth » and « nature », which take part in what may be called the regime of ideal nature, embodied by the ancient model of Greek tragedy. Nature encapsulates the notions of purity and sensitive transparency of morality and truth, through a dynamic conception of history. Diderot’s aesthetics looks for the truth of art, both in painting and drama writing or acting. The Paradoxe sur le comédien gives a definition of truth as « the correspondence of action, speech, face, voice, gesture, with an ideal pattern designed by the poet, which is sometimes overstressed by the actor ». In the 1770’s, Diderot enriches the ancient pattern with exotic primitivism, evolving towards the ideal of naïveté, but which remains nourished by culture and calls for a realization in the present: the imagination of authors and performers thus takes a detour to regenerate forms and aims for a universal language through art, which is accessible to readers and spectators.